Numerical study of using multi-direction angle wire mesh as a confinement system for confined masonry under horizontal cyclic loads - Muhammad R. Hidayat; Ahmad B. Habieb; Wahyuniarsih Sutrisno (Journal of Civil Engineering, 2023)
Indonesia was located in a seismically active region and was situated between three tectonic plates. The construction resilience that met the requirements was necessary in earthquake-prone areas. The purpose was to protect and reduce the risk of severe damage caused by significant seismic loads. However, more than 70% of buildings in developing countries like Indonesia utilized the Confined Masonry (CM) structural system. The implementation of CM systems in Indonesia often led to fatal damages during earthquakes. Due to the severity of these damages, the addition of reinforcement systems to CM became one of the options to address the shortcomings of the CM system. There were various types of materials that could be used as reinforcement, such as steel cages, polymers, polypropylene bands, bamboo meshes, and plastic materials. This study investigated the utilization of ferrocement layers as reinforcement material for CM structural system panels. The specimen panels used had a width of 2300 mm and a height of 1370 mm. The specimens in the research were numerically modeled using the ABAQUS/explicit program. The research variation focused on the influence of the wiremesh sheet orientation angle. The number of variations for the ferrocement layer was one layer with angle configurations of 0, 45, and 60 degrees. This reinforcement layer was applied to one side of the CM panel. As a comparison, results from the control specimen were included. The hysteresis curve, energy dissipation, stiffness degradation, and damage patterns were evaluated in this research.